Free-breathing dynamic T1WI using compressed sensing-golden angle radial sparse parallel imaging for liver MRI in patients with limited breath-holding capability. Issue 152 (July 2022) - Young Park, Jin; Min Lee, Sang; Sub Lee, Jeong; Chang, Won; Hee Yoon, Jeong
Highlights: CS-GRASP controlled motion artifact in dynamic T1WI successfully for the group only with non-cooperative patients. The overall image quality at the free-breathing LAP was lower for non-cooperative patients than the group consisting of both cooperative and non-cooperative patients, whereas image quality was not significantly different at the precontrast and portal venous phases between the two groups. As regards intra-individual comparison, the precontrast phase yielded the lowest image quality and highest incidence of streak artifact, followed by the late arterial phase and portal venous phase respectively. Abstract: Purpose: Evaluating the performance of free-breathing dynamic T1-weighted imaging (T1WI) using compressed sensing golden-angle radial sparse parallel imaging (CS-GRASP) in non-cooperative patients compared with a general group. Method: This retrospective study included patients who underwent gadoxetic acid-enhanced liver MRI using CS-GRASP at 3 T between March 2018 and October 2019. Patients were divided chronologically, into one of two groups: Group 1, who underwent MRI during the sequence implementation period regardless of breath-hold capability; and Group 2, who underwent MRI from June 2018 due to limited breath-hold capability. Three radiologists evaluated motion and streak artifacts as well as overall image quality on a four-point scale at the precontrast phase, late arterial phase (LAP) and portal venous phase (PVP). Intra-individual comparisons were made between sequences in each group. Results: We identified 102 patients, who were divided into either Group 1 (n = 41) or 2 (n = 61). For the LAP, the former group had higher image quality (3.22 ± 0.65 vs. 2.95 ± 0.61, P  < 0.001) and less streak artifact (2.96 ± 0.56 vs. 2.74 ± 0.57, P  = 0.001) than the latter. However, there was no significant difference between the two groups regarding either the proportion of patients with acceptable motion artifact, at 92.7% (38/41) for Group 1 vs. 96.7% (59/61) for Group 2, or that of patients with acceptable image quality at 80.5% (33/41) for Group 1 vs. 65.6% (40/61) for Group 2 ( P  > 0.05). In intra-individual comparisons, portal phase showed the highest image quality than the others in both groups ( P  < 0.001). Conclusions: Acceptable image quality for the LAP in non-cooperative patients was provided with a success rate of over 50% via free-breathing T1WI using CS-GRASP.